Bacterial Causes Conjunctivitis in Children, Study the Resistance to Antimicrobials and The Effect of Breast Milk on Isolated Bacteria - Al-Kalifawi, Esam. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study Isolated Pathogenic bacteria which causes Conjunctivitis in Children with ages between less than 3 year to17 years, admitted to Ibn Al-Haitham Eye Specialist Hospital. 102 cases were collected which include 69 Male Formed (68%) and 33 Female Formed (32%). The result of the recent study shows that the highest percentage of Male was 21% for 1113year ages and the lowest percentage was 3% for less than 3 year to 5 year ages. In Female the highest percentage was 15% for 9-11year ages and the lowest percentage was 1% for 1517year ages. In this study fifty tow isolates were identified, Gram Positive Bacteria were Predominant compared with Gram Negative Bacteria. With 32 isolates which formed (62%) whereas the number of Gram Negative Bacteria was 20 formed (38%). The Antimicrobial Susceptility test to commonly used Antimicrobial showed that the most isolated Bacteria were Resistance to Antimicrobial (Ampicillin, Erythromycin, Gentamicin and Chloramphenicol Base) and Sensitive to (Cephalothin, Ciprofloxacin, Levofloxacin, Norfloxacin, Ofloxacin and Tobramycin). The Antimicrobial Susceptility test of Staphylococcus spp. to Oxacillin showed the predominant of Oxacillin-Sensitive Staphylococcus which (92%) whereas the percentage of Oxacillin -Resistant Staphylococcus was (8%).The Effect of Breast Milk on 52 Isolates Showed the Efficiency of Breast Milk on almost isolates. The growths of thirty five (67%) isolates were inhibited while there was no effect on 17 (33%) isolates. The results of this study concluded that Breast Milk has Antimicrobial Activity against Gram positive and Gram negative Bacteria.